2010
DOI: 10.1007/s00284-010-9724-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term UV-B and UV-C Radiations Preferentially Decrease Spermidine Contents and Arginine Decarboxylase Transcript Levels of Synechocystis sp. PCC 6803

Abstract: To investigate the short term effect of ultraviolet (UV) radiations on changes in pigments and polyamine contents, Synechocystis sp. PCC 6803 cells after exposure to UV-radiation were extracted by dimethylformamide and perchloric acid for pigments and polyamines determination, respectively. Cell growth was slightly decreased after 1 h exposure to UV-A and UV-B radiations. UV-C had little effect on cell growth despite the decrease of photosynthetic rate by about 18%. UV-A and UV-B decreased the contents of chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Typically when cellular PA contents are up, their catabolism also increases, the levels of H 2 O 2 increase, and various ROS as well as the antioxidant systems (enzymes and metabolites) are also up, hence their roles in preventing damage from stress are beneficial as well as deleterious. The role of PAs in augmenting antioxidant based defense systems to impart tolerance against heavy metals, UV and other stresses that are potent inducers of superoxide molecules causing oxidative damage to the living cells have been reported in several studies (Bouchereau et al, 1999; Groppa et al, 2007; Thangavel et al, 2007; Mapelli et al, 2008; Rakitin et al, 2009; Jantaro et al, 2011; Pothipongsa et al, 2012; Chmielowska-Bąk et al, 2013; Mandal et al, 2013; Scoccianti et al, 2013). This is consistent with the diverse roles of PAs including the fact that an increase in cellular PA titers contributes to both sides of the ROS-antioxidant equation under conditions of stress.…”
Section: Reactive Oxygen Species and Polyamine Catabolismmentioning
confidence: 96%
“…Typically when cellular PA contents are up, their catabolism also increases, the levels of H 2 O 2 increase, and various ROS as well as the antioxidant systems (enzymes and metabolites) are also up, hence their roles in preventing damage from stress are beneficial as well as deleterious. The role of PAs in augmenting antioxidant based defense systems to impart tolerance against heavy metals, UV and other stresses that are potent inducers of superoxide molecules causing oxidative damage to the living cells have been reported in several studies (Bouchereau et al, 1999; Groppa et al, 2007; Thangavel et al, 2007; Mapelli et al, 2008; Rakitin et al, 2009; Jantaro et al, 2011; Pothipongsa et al, 2012; Chmielowska-Bąk et al, 2013; Mandal et al, 2013; Scoccianti et al, 2013). This is consistent with the diverse roles of PAs including the fact that an increase in cellular PA titers contributes to both sides of the ROS-antioxidant equation under conditions of stress.…”
Section: Reactive Oxygen Species and Polyamine Catabolismmentioning
confidence: 96%
“…Jantaro et al. () showed that UV‐B and UV‐C can reduce total PA levels by 25%–50% in the cyanobacterium Synechocystis sp., while stimulating an increase in PUT and SPM 3‐ to 8‐fold, respectively. Concurrently, total ADC gene expression decreased, but ADC 1 gene expression and ADC protein levels increased.…”
mentioning
confidence: 99%
“…In this case, UV‐A radiation induced the expression of the ADC1 gene, indicating that ADC1 is the main gene involved in UV‐A protection by increasing the amount of free PAs (Jantaro et al. ).…”
Section: Functions Of Polyaminesmentioning
confidence: 96%
“…At the same time, ADC mRNA decreased, while ADC activity did not change (Jantaro et al. ). Under closer observation, it became clear that the induction of transcription depended upon the wavelength of the UV radiation.…”
Section: Functions Of Polyaminesmentioning
confidence: 97%
See 1 more Smart Citation